Effects of birth weight, finishing feeder design, and dietary astaxanthin and ractopamine HCl on the growth, carcass, and pork quality characteristics of pigs; and meta-analyses to improve the prediction of pork fat quality - Bergstrom, Jonathan Robert (Kansas State University, 2011)
Eleven-thousand one-hundred eighty-five pigs were used in 11 experiments to determine effects of birth-weight, feeder design, and dietary astaxanthin (AX) and ractopamine HCl (RAC) on growth, carcass, and pork quality characteristics of pigs. Also, data from 27 experiments were used in meta-analyses to improve prediction of pork fat iodine value (IV). In Exp. 1, increased birth-weight resulted in greater (quadratic, P < 0.05) pre-weaning survivability, ADG, final BW, and likelihood of achieving full-value market at 181-d of age. In Exp. 2, 3, 4, 6, 7, and 8, pigs using the wet-dry feeder (WD) had greater (P < 0.05) ADG, ADFI, and final BW than those using the conventional dry feeder (CD). Pigs using WD had poorer (P < 0.05) G:F in Exp. 3 and 4, and increased (P < 0.05) HCW and backfat depth in Exp. 3, 4, 6, and 7, compared to pigs fed using CD. In Exp. 5, pigs using WD from 19 to 38 kg had decreased (P < 0.02) ADFI and better G:F than pigs using CD. Increased feeder opening of WD increased (P < 0.05) ADG, ADFI, and final BW in Exp. 5, 6, and 7; as well as HCW and backfat depth in Exp. 6 and 7. Reducing WD opening at 28- and 56-d in Exp. 7 decreased (P < 0.05) ADG, ADFI, and backfat depth. Different openings of CD had little effect on performance in Exp. 5 and 6. In Exp. 8, changing water-source of WD to a separate location during late-finishing reduced (P < 0.05) overall ADG, ADFI, and final BW. Limited responses to AX were observed in Exp. 9, 10, and 11, but ADG, G:F, final BW, HCW, and fat-free lean were improved (P < 0.05) for pigs fed RAC in Exp. 10 and 11. Total color change during retail display of LM chops for gilts and pigs fed RAC was reduced (P < 0.05) in Exp. 10 and 11, indicating their color shelf-life improved. In the meta-analyses, models using dietary PUFA with ADG, BW, or backfat depth improved the fat IV prediction from R2 = 0.45 to R2 = 0.90.
Keywords: Astaxanthin; Birth weight; Feeder design; Litter; Pigs; Pork fat quality; Animal Sciences (0475)